The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12883-021-02160-5
|View full text |Cite
|
Sign up to set email alerts
|

Experience using mTOR inhibitors for subependymal giant cell astrocytoma in tuberous sclerosis complex at a single facility

Abstract: Background Subependymal giant cell astrocytoma (SEGA) is occasionally seen in tuberous sclerosis complex (TSC). Two main options are currently available for treating SEGA: surgical resection or pharmacotherapy using mammalian target of rapamycin inhibitors (mTORi). We hypothesized that opportunities for surgical resection of SEGA would have reduced with the advent of mTORi. Methods We retrospectively reviewed the charts of patients treated between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In our case, the intraoperative level of CSF protein was as high as 123 mg/dL, which is consistent with findings from studies on hydrocephalus associated with other benign tumors. Although the nature of the tumors differs between vestibular schwannoma and SEGA, the similarity in elevated CSF protein levels suggests that the underlying mechanism of hydrocephalus may involve impaired CSF circulation or increased osmotic pressure within the ventricles, rather than just physical obstruction [ 2 , 17 ]. This case report supports the hypothesis that factors other than tumor size contribute to hydrocephalus in patients with SEGA and TSC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, the intraoperative level of CSF protein was as high as 123 mg/dL, which is consistent with findings from studies on hydrocephalus associated with other benign tumors. Although the nature of the tumors differs between vestibular schwannoma and SEGA, the similarity in elevated CSF protein levels suggests that the underlying mechanism of hydrocephalus may involve impaired CSF circulation or increased osmotic pressure within the ventricles, rather than just physical obstruction [ 2 , 17 ]. This case report supports the hypothesis that factors other than tumor size contribute to hydrocephalus in patients with SEGA and TSC.…”
Section: Discussionmentioning
confidence: 99%
“…Subependymal giant cell astrocytoma (SEGA) associated with tuberous sclerosis complex (TSC) occurs in 5-20% of TSC patients [ 1 ]. Approximately 4-14% of these cases present with hydrocephalus, and ventricular dilatations are seen in 85% [ 2 , 3 ]. Studies have indicated that the mechanism by which SEGA causes hydrocephalus involves enlargement of the SEGA leading to blockage of the foramen of Monro and the subsequent development of hydrocephalus [ 3 - 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…mTOR inhibitors were recently approved in the EU, USA, and Japan [8]. Besides focal-onset seizures, everolimus is currently approved for treating SEGA and LAM and used as an off-label treatment for CR reduction [9][10][11][12][13]. Sirolimus is approved only as LAM therapy in patients with TSC, while its impact on seizure frequency is not yet determined.…”
Section: Introductionmentioning
confidence: 99%
“…New rapamycin analogs (Rapalogs) have been developed for TSC patients and other diseases with mTORC1 hyperactivation. Everolimus, the hydroxyethyl ester of rapamycin, was successful in shrinking SEGAs [11,12]. Long-term Everolimus treatment efficiently reduced SEGAs and prevented new SEGAs formation [13].…”
Section: Introductionmentioning
confidence: 99%